Financial Crises and Climate Change - Jalles, João Tovar (2020)
We empirically assess by means of the local projection method, the impact of financial crises on climate change vulnerability and resilience. Using a new dataset covering 178 countries over the period 1995–2017, we observe that resilience to climate change shocks has been increasing and that advanced economies are the least vulnerable. Our econometric results suggest that financial crises (particularly systematic banking ones) tend to lead to a short-run deterioration in a country´s resilience to climate change. This effect is more pronounced in developing economies. In downturns, if an economy is hit by a financial crisis, climate change vulnerability increases. Results are robust to several sensitivity checks.